2010
DOI: 10.1200/jco.2009.26.1602
|View full text |Cite
|
Sign up to set email alerts
|

Akt Phosphorylation at Ser473 Predicts Benefit of Paclitaxel Chemotherapy in Node-Positive Breast Cancer

Abstract: pAkt significantly predicts disease-free benefit from the sequential addition of paclitaxel to AC chemotherapy in patients with node-positive breast cancer. Patients with pAkt-negative breast tumors do not appear to benefit from the addition of paclitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Taxanes have demonstrated great efficiency in the treatment of breast cancer and are widely used in the adjuvant, neo-adjuvant, and metastatic settings [2][3][4][5][6][7]. However, predicting taxane benefit [8][9][10][11][12][13] using conventional histoclinical factors has been controversial and no molecular predictor has been clearly identified [14][15][16][17][18]. Thus, ER, HER2, b-tubulin isotypes, p53, or MAP-Tau expression, which all had been suggested to regulate Taxsensitivity, were not validated as surrogate markers for drug efficacy and none is currently used in the clinic for selecting Tax treatment [4,8,9,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Taxanes have demonstrated great efficiency in the treatment of breast cancer and are widely used in the adjuvant, neo-adjuvant, and metastatic settings [2][3][4][5][6][7]. However, predicting taxane benefit [8][9][10][11][12][13] using conventional histoclinical factors has been controversial and no molecular predictor has been clearly identified [14][15][16][17][18]. Thus, ER, HER2, b-tubulin isotypes, p53, or MAP-Tau expression, which all had been suggested to regulate Taxsensitivity, were not validated as surrogate markers for drug efficacy and none is currently used in the clinic for selecting Tax treatment [4,8,9,16,[19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Another analysis by my group of the B28 study looked at Akt phosphorylation, finding that patients with tumors that were Akt ϩ ER Ϫ did have a benefit with taxane therapy whereas those whose tumors were phosphorylated Akt Ϫ did not [26] (Fig. 6).…”
Section: Other Biomarkers and Response To Therapymentioning
confidence: 99%
“…This finding was echoed by Grell et al ,37 who showed that patients with HER2-positive metastatic breast cancer that expressed cytoplasmic and nuclear pAkt treated with trastuzumab had a better overall survival. Furthermore, Yang et al 38 demonstrated that patients with pAkt-positive breast cancers have a 26% improvement in disease-free survival or a 20% improvement in overall survival, with the sequential addition of paclitaxel to doxorubicin plus cyclophosphamide adjuvant chemotherapy in patients with node-positive early breast cancer. These apparent discrepancies in the outcome of patient with pAkt expression tumours may relate to differences in patient cohort characteristics, for example, breast cancer versus NSCLC, early versus late disease, as well as to variations in methodology and antibody selection.…”
Section: Discussionmentioning
confidence: 99%